(untitled) (Innovative professional education, 2024)
The question of improvement of the motivation of specialists in the field of special and inclusive education to work in online format according to European experiences and practiceshas been raised. The variability of professionally important qualities of specialists in the social field is related to the complexity and diversity of the functions they perform in the conditions of interaction with different contingents in constantly changing social and professional conditions of activity. The values of online education in the global and national dimensions have been delighted. An analytical review of research’s results has been conducted.